1990
DOI: 10.1002/jor.1100080610
|View full text |Cite
|
Sign up to set email alerts
|

Torsional strength reduction due to cortical defects in bone

Abstract: This study correlated torsional strength reduction with circular defect size in cortical bone, to define the "stress riser" and "open-section" effect of the defects. The experimental model was developed and verified. Circular defects from 10 to 60% of bone diameter were then created in paired sheep femora and the bones loaded to failure. Contrary to theory, this experimental study suggests that small defects (10%) of bone diameter cause no significant torsional strength reduction. A 20% defect caused a 34% dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
102
2
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(117 citation statements)
references
References 18 publications
4
102
2
2
Order By: Relevance
“…Several previous studies have analyzed the effect of transcortical holes. 26,44,[53][54][55][56][57][58][59] We suspect that inclusion of a stress concentration factor would improve our strength estimates. However, the clinical setting was more closely replicated by not correcting for this.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have analyzed the effect of transcortical holes. 26,44,[53][54][55][56][57][58][59] We suspect that inclusion of a stress concentration factor would improve our strength estimates. However, the clinical setting was more closely replicated by not correcting for this.…”
Section: Discussionmentioning
confidence: 99%
“…Such procedures prevent the formation of regions of stress concentration in their in vitro study of sheep femurs demonstrated that transcortical drill holes decreased endurance against torsional forces 16,19 . It is known that in humans, the thickness of the cortical wall decreases with age 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown that fractures do not generally occur with small holes, indicating that the effect of stress concentration increases with an increase in the size of the hole. In addition, when the geometry of round holes is compared with that of non-round holes, a decrease in stress concentration is observed 19 .…”
Section: Discussionmentioning
confidence: 99%
“…While there are concerns that the integrity of the femoral neck might be compromised, there were no femoral neck fractures or clinically significant screw failures in our series. Biomechanical tests have demonstrated that cortical defects less than 20% of the diameter of a long bone do not incur a significant stress riser or weaken the bone, predisposing it to fracture [6,7]. The average femoral neck diameter is 40-50 mm and insertion of 4-mm cancellous cross-locking screws is well within the 20% margin of safety.…”
Section: Discussionmentioning
confidence: 99%
“…When late removal is performed, the bone has had a chance to develop adaptive strain patterns, and the strength reduction is less than that of acute removal. Furthermore, within 6 weeks of screw removal, the strength approaches that of normal bone [6]. Recently, the biomechanical performance of cephalad-positioned intramedullary nails with screws placed into the medial femoral neck was reported to be equal to that of reconstructiontype nails under both axial and torsional loads.…”
Section: Discussionmentioning
confidence: 99%